180k views
4 votes
An equation is shown below: 4c + 2(x-3) = 4x + 2x - 11 Part A: solve the equation and write the number of solutions. Show all the steps. Part B: Name one property you used to solve this equation.

User Whaleberg
by
4.9k points

2 Answers

5 votes
There is NO SOLUTION. We used the distributive property to distribute the 2(x-3).

Explanation:
4x+2(x-3)=4x+2x-11
4x+2x-6=4x+2x-11 Distribute 2 by x-3
6x-6=6x-11 Combine Like Terms
-6=-11 Subtract Weaker X
-6≠-11 Find Answer

-6 does not equal -11, so there is no solution to this equation.
User Davetapley
by
5.3k points
3 votes

Part A: first multiply 2 by x and -3 → combine all like terms → Add 6 on both sides → subtract 6x from both sides.

Your final answer should be -5

step by step: 4x + 2(x-3) = 4x + 2x - 11

4x +2x -6 = 4x + 2x - 11

6x -6 = 6x - 11

6x = 6x -11 +6

6x = 6x -5

6x-6x= -5

0 = -5

Part B: Add all like terms.

Hope this helps! :)

User Nakx
by
5.4k points